Managing the Agricultural Sector Through Muzara’ah: Implementing an Islamic Economic Participatory Mode of Financing - Bangash, Amjad Ullah Jan (International Journal of Islamic Business & Management, 2020)
The tremendous growth of Islamic banking has transformed a relatively new industry into a robust and widespread reality on the ground. Several Islamic financial institutions (IFIs) operate in different countries of the world and several Islamic modes of financing have been developed; however, most cater to the needs of commercial businesses, and personal finance. Few IFI products have been made available to support the agricultural sector. One rarely used product is Salam (a kind of sale in which farmers sell their product in advance, before the season’s harvest, to get funding for farming inputs as well as for their livelihood expenses), which, however, is of limited use due to a range of limitations. Hence, there remains a need for a product which is shari’a compliant and acceptable to IFIs as well as the end users, that is, the farmers. This paper proposes an Islamic model suitable for entrepreneurs, farmers and IFIs. A mixed-methods research methodology is applied: while the study is mainly qualitative, a quantitative approach was applied to the data obtained through questionnaires. The general finding of this paper is that there is a need to have a shari’a-compliant financing model to be based on a participatory basis, in place of the debt-based modes which are currently in extensive use by IFIs. Therefore, I selected the Muzara’ah (sharecropping) concept as the basis of a model to help the agricultural economy and the Islamic banking industry. The reason for choosing the participatory over the debt-based mode is that the latter cannot bring about any real change, as I shall demonstrate from the particular perspective of Pakistan. Research into the demography of the Pakistani agricultural sector, on the other hand, demonstrates that the Muzara’ah model can be used anywhere in the world. The paper also aims to understand the effects on this sector of the use of financing by both commercial and Islamic banks, the strengths and weaknesses of financial intermediation, and the challenges faced by Islamic banks as concerns financing the agricultural sector. This research paper is divided into four sections. The first introduces and debates the position of agriculture in Pakistan; the ways in which commercial banks extend loans to this sector, and the socio-economic effects of such loans; and the different existing financing models being used for this sector and their respective drawbacks. The section also presents a brief discussion of Islamic banking and its advantages; different Islamic modes of financing; and how Islamic banks are supporting the agricultural sector in Pakistan. Furthermore, it argues that there is a global need for an alternative Islamic model to finance the agricultural sector, and that this need is particularly pressing in Pakistan. The second section discusses the Muzara’ah model, through an extensive review of the extant Islamic literature, encompassing, but not limited to, the definition of Muzara’ah, the Islamic basis for the practice and Islamic juristic views, as well as how Muzara’ah worked in a previous age. Moreover, this section discusses the similarities and differences in opinion among Islamic jurists (experts in Islamic law) about the validity of Muzara’ah. The focus of this section is on finding a consensus as to the most common and viable mode of Muzara’ah which is acceptable to a majority of jurists.The third section surveys agriculture in Pakistan, as well as the opinions and perspectives of farmers, bankers and other stakeholders to inform the proper development of an Islamic Muzara’ah sharecropping model. Practical research was carried out in Kohat, one of the cities of Pakistan, which is famous for its guava, wheat and maize production. A description of the fieldwork is also presented in this section.The fourth section draws on all the above information to develop a model based on the concept of Muzara’ah which can be feasibly implemented in the Islamic banking industry. Moreover, it presents a discussion of the strengths and weaknesses of the model and provides suggestions and recommendations about how it should be rolled out. The needs of end users, such as farmers and growers, are addressed, and a discussion is presented of how the product better meets their needs than the other products which are currently available to them.